Oral Glucose Tolerance Test in Patients with Cystic Fibrosis Compared to the Overweight and Obese: A Different Approach in Understanding the Results - Mirela Mogoi; Liviu Laurentiu Pop; Mihaela Dediu; Ioana Mihaiela Ciuca (MDPI AG, 2022)
(1) Background: In cystic fibrosis (CF), the oral glucose tolerance test (OGTT) is recommended from 10 years old annually to screen and diagnose cystic fibrosis-related diabetes (CFRD). Alternative OGTT characteristics (glucose curve shape, time to glucose peak, one-hour glucose value, and three-hour glucose value with the new shape curve) were studied in other populations considered at high risk for diabetes; (2) Methods: The study analyses classical and alternative OGGT characteristics from 44 children (22 CF, 22 obese without CF), mean age: 12.9 ± 2.2 years evaluated in a single-center from Romania. (3) Results: In 59.1% of children with CF, the predominant OGTT pattern was: abnormal glucose metabolism or CFRD, with a monophasic curve shape, a late peak glucose level, and 1 h glucose ≥ 155 mg/dL, showing a very different pattern compared with sex and age-matched obese children. Statistical estimation agreement between the late glucose peak (K = 0.60; p = 0.005), the 1 h glucose ≥ 155 mg/dL during OGTT (K = 0.69, p = 0.001), and the classical method of interpretation was found. (4) Conclusions: Late peak glucose and 1 h glucose level ≥ 155 mg/dL during OGTT can be used for diagnosing the early glucose metabolism alteration in children with CF.